1995
DOI: 10.1073/pnas.92.5.1714
|View full text |Cite
|
Sign up to set email alerts
|

Soluble type II interleukin 1 (IL-1) receptor binds and blocks processing of IL-1 beta precursor and loses affinity for IL-1 receptor antagonist.

Abstract: The human IL-1 gene family comprises IL-la, IL-1f3, and IL-1 receptor antagonist (IL-lra). All three share limited amino acid identity and bind to the same receptors on different cell types (1). In the case of IL-ia and IL-11, ligand-receptor interaction activates signaling pathways involved in both immune and inflammatory responses. Binding of IL-lra to the IL-1 receptor (IL-lR) does not trigger signal transduction, and the actions of IL-la and IL-113 are blocked by this unique antagonist protein (2).Both IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
131
0
4

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(136 citation statements)
references
References 33 publications
1
131
0
4
Order By: Relevance
“…This observation emphasizes the notion that membrane IL-1RII can act as a ligand sink, whereas on the other hand it sheds some light on the conformational requirements for an effective interaction between IL-1RII and IL-1RAcP. Results from earlier studies show that wtIL-1RII in its membrane form can bind IL-1␣ and IL-1␤, but not the 31-kDa precursor form of IL-1␤ (17). Once released from the surface by proteolytic cleavage, the ligand-binding characteristics of IL-1RII change dramatically.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This observation emphasizes the notion that membrane IL-1RII can act as a ligand sink, whereas on the other hand it sheds some light on the conformational requirements for an effective interaction between IL-1RII and IL-1RAcP. Results from earlier studies show that wtIL-1RII in its membrane form can bind IL-1␣ and IL-1␤, but not the 31-kDa precursor form of IL-1␤ (17). Once released from the surface by proteolytic cleavage, the ligand-binding characteristics of IL-1RII change dramatically.…”
Section: Discussionmentioning
confidence: 83%
“…To date, the IL-1-inhibitory function of the IL-1RII has been clearly demonstrated for the soluble form (17,22,32) and in systems in which both membrane and sIL-1RII were present (22,33,34). It still remains a matter of investigation whether the functional role of membrane IL-1RII is only that being a source for soluble inhibitory receptor or whether membrane IL-1RII itself contributes to the negative regulation of IL-1 activity by acting as ligand sink, as suggested by indirect data (12,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not lead to signal transduction because this receptor lacks the intracellular Toll-IL-1 receptor domain that is crucial for MyD88 binding (16)(17)(18). Therefore, the type II receptor is a decoy receptor as has been described for its transmembrane and soluble forms (19).…”
mentioning
confidence: 99%
“…It is generally accepted that occupation of only 1% of the IL-1RI by IL-1 instigates full-blown cell activation, and as a consequence, relatively high amounts of IL-1Ra (100-1,000-fold molar excess) are required to fully block IL-1. Fortunately, IL-1Ra binds poorly to IL-1RII (19), and both IL-1Ra and soluble IL-1RII (sIL-1RII) cooperate in IL-1 inhibition. We have demonstrated that administration of IL-1Ra protein or the IL-1Ra gene ameliorates disease in several models of experimental arthritis, with a profound protective effect against cartilage and bone destruction (20,21).…”
mentioning
confidence: 99%